Vpliv 6-mesečnega vadbenega programa na vzdržljivost in parametre aerobne sposobnosti odraslih žensk - Škof, Branko (Zdravstveno varstvo, 2010)
The aim of the study was to determine the effect of a complex six-month recreational running programme on the aerobic capacity of middle-aged women with poor physical fitness, and to establish which physiological and biochemical parameters are affected by the selected training. The study included 11 females with the average age of 48.7 11.9 years. Their body height was 165.5 7,1 cm, body mass 74.1 10,7 kg and body fat percentage 25,6 5,6 %. The maximum oxygen uptake was 33.7 6,1 mlO2/kg/min. The training programme took place four times a week over a 24-week period. The endurance training consisted of running, walking and walking uphill. Another important element of the programme were exercices for muscle strength and flexibility. Before and after the training programme, the participants underwent anthropometrical measurements and measurements of functional and biochemical parameters using a loading test on a treadmill. All the selected running endurance parameters improved by 10 % to 17% (P<0.01). VO2max increased by 360 ml/min or 5.5 ml/kg/min, which means 14.1 1,2 % or 16.9 1,5 % (P<0.001). The increase in the runners'' aerobic capacity after completing the training protocol was mainly due to improved cardiac function parameters. The heart stroke volume rose by 11.5 3,1 %, i.e. from 80.2 11.5 ml to 89.4 7.6 ml; (P<0.05). The study results confirmed the efficiencyof the complex running programme in the selected sample of middle-aged women with poor physical fitness. It not only brought about a positive biological response with an indirect decrease in health risk, but also encouraged the participants to adopt a healthy and active lifestyle.
Keywords: aerobne sposobnosti; učinki; vadba; vzdržljivost; woman; ženske